2022
DOI: 10.1186/s12889-022-13161-5
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of stress appraisal and problem-focused coping: associations with compliance with public health recommendations during the COVID-19 pandemic

Abstract: Background Given prior research finding that young adults are less likely to engage in recommended public health behaviors (PHBs) than older adults, understanding who is and is not likely to engage in PHBs among young adults is crucial to mitigating the effects of the COVID-19 pandemic. Drawing on the Transactional Theory of Stress and Coping, this study examined how typologies of stress appraisal (SA) and problem-focused coping (PFC) among young adults were associated with compliance with publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
3
0
2
Order By: Relevance
“…In the health belief model, age can modify perceived risk and susceptibility. The role of age in the adoption of preventive behaviours has been consistently found in studies showing that young adults are less likely to adopt public health behaviours 29 30. In our study, the age difference between groups (adherence vs non-adherence) was too small (31 years vs 36 years) to implicate higher perceived frailty or vulnerability in older respondents.…”
Section: Discussionmentioning
confidence: 46%
“…In the health belief model, age can modify perceived risk and susceptibility. The role of age in the adoption of preventive behaviours has been consistently found in studies showing that young adults are less likely to adopt public health behaviours 29 30. In our study, the age difference between groups (adherence vs non-adherence) was too small (31 years vs 36 years) to implicate higher perceived frailty or vulnerability in older respondents.…”
Section: Discussionmentioning
confidence: 46%
“…Consequently, their enhanced hope may enable male participants to navigate through challenging life events more effectively, leading to improved school adjustment. For instance, a study by Landy et al [ 55 ] found that male adolescents tend to engage in problem-focused coping strategies, which can contribute to their higher levels of hope and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Afrontamiento centrado en el problema. En esta tipología se trata de cumplir con las pautas y normas recomendadas para hacer frente al problema, en lugar de evitarlas (Landy et al, 2022). Una investigación encontró que el afrontamiento centrado en el problema y centrado en la emoción se relacionan con una buena salud mental (Li, 2020;Li et al, 2021).…”
Section: Issn-l: 2027-1786unclassified